A participatory approach to iteratively adapting game design workshops to empower autistic youth - Gillespie-Lynch, Kristen; Grossman, Eliana; Herrell, Jessye; Riccio, Ariana; Delos Santos, Jin; Biswas, Sharang; Kofner, Bella; Dwyer, Patrick; Rosenberg, Beth; Hwang-Geddes, Lillian; Hurst, Amy; Martin, Wendy B.; et al. (Frontiers in Education, 2023)
Autistic people face systemic barriers to fair employment. Informal learning may promote the self-determination transition-age autistic youth need to overcome and/or transform these barriers. This report focuses on the iterative process of developing video game design workshops, guided by feedback from autistic students, about instructional strategies they found engaging. This study is part of a three-year-long NSF-funded program of research that seeks to empower autistic youth to move toward successful careers by teaching educators how to more effectively guide them. In the Summer of 2021, educators at an award-winning NYC-based, not-for-profit, education program, Tech Kids Unlimited (TKU) collaborated with researchers, including autistic students, to iteratively develop and assess two online game design workshops for transition-age autistic youth. Participants selected which workshop they were available for (Workshop 1: n = 18; M age = 16.78 years; Workshop 2: n = 16; M age = 16.56 years). Students in Workshop 2 had more varied support needs and were less motivated to learn video game design than students in Workshop 1. Students completed assessments before and after each workshop and rated their interest in specific workshop activities after each activity. Guided by data from Workshop 1, we revised instructional strategies before conducting Workshop 2. We found little evidence for our hypothesis that attentional style would impact educational engagement. However, video game design self-efficacy and self-determination were often positively associated with engagement. Two industry speakers, one of whom was autistic, were among the highest-rated activities. As hypothesized, video game design self-efficacy and self-determination (and unexpectedly) spatial planning improved from pre- to post-test following Workshop 1. Despite our efforts to use what we learned in Workshop 1 to improve in Workshop 2, Workshop 2 did not lead to significant improvements in outcomes. However, students highlighted instructional strategies as a strength of Workshop 2 more often than they had for Workshop 1. Educators highlighted the importance of group “temperature checks,” individualized check-ins, social-emotional support for students and educators, and fostering a positive atmosphere. Findings suggest that interactive multimodal activities, stimulating discussions, and opportunities to engage with neurodivergent industry professionals may engage and empower diverse autistic youth.